Coral diversity on artificial reef from coconut shells in northern Bali, Indonesia - Eghbert Elvan Ampou; Gede Iwan Setiabudi; Nuryani Widagti; I Nyoman Dodik Prasetia (Society for Indonesian Biodiversity, 2020)
Artificial reef from natural product bioreeftek is very easy to apply and can be found in many tropical coastal areas namely coconut shells with natural coral recruitment. The purpose of this study was to calculate the percentages of coral cover, ratio and clustering. At the two research sites in North Bali, Pemuteran - Napoleon reef, depth 5-6m-reef slope found 13 species of live coral from 9 bioreeftek: Porites sp 32%, Pocillopora damicornis 13%, Seriatopora sp 10%, Acropora palifera, Acropora sp, Goniastrea sp, Favia sp, Pachyseris sp = 6%; Montipora sp - Echinopora sp - Favites sp - Fungia fungites and Leptoseris sp = 3%. At the Lovina - Adirama Temple, depth of 6m-reef flat was found in 14 species from 14 bioreeftek: Acropora palifera 24%, Pocillopora damicornis 21%, Porites sp 7%, Montipora sp 4% - Acropora sp - Pavona sp = 3%, Platygyra sp 2%, Acropora humilis - Millepora = 1%. Cluster Analysis showed all corals on two sites are correlated in percent cover, characteristics, influences and occurrences. Artificial reefs with natural materials such as coconut shells are necessary developed in addressing the degradation of coral reef ecosystem. The added value of bioreeftek is insertion/inserted method of coral.